1977
DOI: 10.1111/j.1469-7610.1977.tb00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline and Methylphenidate Treatment of Behaviorally Disordered Children

Abstract: THIS STUDY is one in a series of continuing investigations Winsberg et aL, 1974b) which seeks to determine the relative effectiveness of various psychotropic drugs in controlling hyperactive/aggressive behaviors among children.In our previous work, we found the psychostimulants (dextroamphetamine and methylphenidate) to be comparable in effectiveness for the treatment of such behavior disorders (Winsberg et al., 1974b), while the tricyclic compound, imipramine, was also found to be effective in a study which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
1
2

Year Published

1978
1978
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 21 publications
0
14
1
2
Order By: Relevance
“…Five studies each reported that stimulants were superior to TCAs (Garfinkel et al, 1983;Gittleman-Klein, 1974;Greenberg et al, 1975;Rapoport et al, 1974), or equal to TCAs (Gross, 1973;Huessy and Wright, 1970;Kupietz and Balka, 1976;Yepes et al, 1977) and three studies reported that TCAs were superior to stimulants (Watter and Dreyfuss, 1973;Werry, 1980;Winsberg et al, 1972). Analysis of response profiles indicate that TCAs more consistently improve behavioural symptoms, as rated by clinicians, teachers and parents than they impact on cognitive function as measured in neuropsychological testing (Gualtieri and Evans, 1988;Quinn and Rapoport, 1975;Rapport et al, 1993;Werry, 1980).…”
Section: What Is the Evidence For Non-stimulants In Adhd?mentioning
confidence: 93%
“…Five studies each reported that stimulants were superior to TCAs (Garfinkel et al, 1983;Gittleman-Klein, 1974;Greenberg et al, 1975;Rapoport et al, 1974), or equal to TCAs (Gross, 1973;Huessy and Wright, 1970;Kupietz and Balka, 1976;Yepes et al, 1977) and three studies reported that TCAs were superior to stimulants (Watter and Dreyfuss, 1973;Werry, 1980;Winsberg et al, 1972). Analysis of response profiles indicate that TCAs more consistently improve behavioural symptoms, as rated by clinicians, teachers and parents than they impact on cognitive function as measured in neuropsychological testing (Gualtieri and Evans, 1988;Quinn and Rapoport, 1975;Rapport et al, 1993;Werry, 1980).…”
Section: What Is the Evidence For Non-stimulants In Adhd?mentioning
confidence: 93%
“…Os resultados encontrados neste estudo coincidem com os verificados por Guardiola ao comparar grupos tratados com imipramina e placebo 17 . Usando as provas de persistência motora como parâmetro da eficácia da AMI, a exemplo de trabalho publicado por Guardiola e colaboradores em 1997 32 , verificamos que amitriptilina se mostra eficaz no tratamento de crianças com SHDA, fato já verificado em estudos feitos por Krakowski 28 , Kupietz e Balka 29 e Yepes e col. 30 .…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…Kupietz e Balka, em ensaio clínico, compararam os efeitos da AMI, metilfenidato (MTF) e placebo sobre o desempenho de 20 crianças com comportamento hiperativo e agressivo observando que tanto AMI quanto MTF apresentaram resposta superior ao placebo 29 . Yepes e colaboradores, usaram AMI em ensaio clínico, comparado com MTF e placebo em 21 crianças com comportamento hiperativo e agressivo, verificando, em ambas as drogas, respostas similares e melhores em relação ao placebo 30 . Spencer, em estudo que avalia e compara as várias opções terapêuticas para a SHDA, cita os trabalhos acima mencionados e refere que pacientes tratados com AMI tiveram resposta similar a dos estimulantes 31 .…”
unclassified
“…AMT has not been extensively researched with children. Although it appears to be effective, it is highly sedative and almost all children appear drowsy (Yepes, Balka, Winsberg, & Bialer, 1977). IMI has been shown to be effective in a number of comparative studies, although it too causes a variety of adverse side effects.…”
mentioning
confidence: 97%
“…However, the sedative effects of AMT raise the question of whether the tricyclics as a class might impair children's ability for attention. Although highly sedative, AMT has been found to facilitate performance on the Continuous Performance Test (CPT) measure of attention (Yepes et al, 1977). Clinically, IMI is less sedative than AMT, but its effect on attention has not been studied.…”
mentioning
confidence: 99%